The Effect of a Curved Non-Motorized Treadmill on Running Gait Length, Imbalance and Stride Angle - Andrew Hatchett; Kaitlyn Armstrong; Brian Parr; Mallory Crews; Charlie Tant (MDPI AG, 2018)
Running on a non-motorized, curved-deck treadmill is thought to improve gait mechanics. It is not known, though, whether the change in gait carries over to running on a motorized treadmill on level ground. To determine the effect of running on a curved non-motorized treadmill (CNT) on gait characteristics, measured during a subsequent bout of running on a traditional motorized treadmill (TMT), sixteen healthy college-aged participants, aged (mean ± SD) 20.4 ± 1.6 years, volunteered to have their gait analyzed while running on a TMT and CNT. After familiarization with, and a warm-up on, both treadmills, each subject completed five 4-min bouts of running, alternating between traditional motorized and curved non-motorized treadmills: TMT-1, CNT-1, TMT-2, CNT-2, and TMT-3. Variables of interest included step length (m), stride length (m), imbalance score (%), and stride angle (°), and were measured using Optogait gait analysis equipment. We found differences in gait characteristics among TMT-1, TMT-2, and TMT-3, which can be attributed to running on the CNT. The results show that running on a CNT resulted in significant changes in gait characteristics (step length, stride length, imbalance score and stride angle). These findings suggest that running on a CNT can significantly influence running gait.